[18F]-fluorodeoxyglucose positron emission tomography of the cat brain: A feasibility study to investigate osteoarthritis-associated pain. Issue 3 (June 2015) - Guillot, Martin; Chartrand, Gabriel; Chav, Ramnada; Rousseau, Jacques; Beaudoin, Jean-François; Martel-Pelletier, Johanne; Pelletier, Jean-Pierre; Lecomte, Roger; de Guise, Jacques A.; Troncy, Eric
Highlights: [ 18 F]-fluorodeoxyglucose positron emission tomography of the cat brain. Brain metabolism of osteoarthritic cats is increased in pain key regions. Brain plasticity occurred in natural OA-associated pain in cats. Sustained nociceptive inputs are present in feline OA-associated pain. Increased activity of the descending pathways is present in feline OA-associated pain. Abstract: The objective of this pilot study was to investigate central nervous system (CNS) changes related to osteoarthritis (OA)-associated chronic pain in cats using [ 18 F]-fluorodeoxyglucose ( 18 FDG) positron emission tomography (PET) imaging. The brains of five normal, healthy (non-OA) cats and seven cats with pain associated with naturally occurring OA were imaged using 18 FDG-PET during a standardized mild anesthesia protocol. The PET images were co-registered over a magnetic resonance image of a cat brain segmented into several regions of interest. Brain metabolism was assessed in these regions using standardized uptake values. The brain metabolism in the secondary somatosensory cortex, thalamus and periaqueductal gray matter was increased significantly ( P ≤ 0.005) in OA cats compared with non-OA cats. This study indicates that 18 FDG-PET brain imaging in cats is feasible to investigate CNS changes related to chronic pain. The results also suggest that OA is associated with sustained nociceptive inputs and increased activity of the descending modulatory pathways.